Lincoln's journey to greatness - Searcher, Victor
Typescript appendix and index (unpublished) for Searcher's book, Lincoln's Journey to Greatness (1960), an account of Lincoln's travel from Springfield, Ill., to Washington, D.C., for his first presidential inauguration.
Journalist and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Inauguration, 1861.; Lincoln, Abraham, -- 1809-1865 -- Travel -- Washington (D.C.); Springfield (Ill.) -- Description and travel; Washington (D.C.) -- Description and travel; Authors; Journalists